125k views
4 votes
For f(x) = 2x+1 and g(x) = 3x-7, find (f-g)(x)

2 Answers

5 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


(f - g)(x) = f(x) - g(x) =


(2x + 1) - (3x - 7) =


2x + 1 - 3x + 7 =


- x + 8

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Thus ;


(f - g)(x) = - x + 8

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Marsmensch
by
5.2k points
7 votes

Answer:

(f - g)(x) = -x + 8

General Formulas and Concepts:

  • Order of Operations: BPEMDAS

Explanation:

Step 1: Define

f(x) = 2x + 1

g(x) = 3x - 7

(f - g)(x) = f(x) - g(x)

Step 2: Simplify

  1. Set up: (f - g)(x) = (2x + 1) - (3x - 7)
  2. Distribute -1: (f - g)(x) = 2x + 1 - 3x + 7
  3. Combine like terms: (f - g)(x) = -x + 8
User William Pourmajidi
by
4.7k points